Study on the Tooth Surface Contact Temperature of Spur Gear - Jiazhi Shen; Xiangfeng Gou; Lingyun Zhu (Jixie chuandong)
Abstract In view of the important influence of tooth surface contact temperature on gear meshing process， the calculation formulas of tooth surface contact temperature of spur gear under four different lubrication conditions are established based on Blok flash temperature theory. The distribution of tooth surface contact temperature along the meshing line and the effects of rotational speed， torque， lubricant viscosity and backlash on tooth surface contact temperature are analyzed. The tooth contact temperature under different working conditions is measured. The numerical results and experimental results show that the contact temperature of the tooth surface reaches the highest at the meshing position and addendum and it is close to the room temperature near the pitch circle. It is found that the contact temperature of tooth surface increases with the increase of lubricant viscosity under EHL condition， but it is opposite under mixed lubrication condition. The lubricant viscosity has no obvious effect on the contact temperature of tooth surface under boundary lubrication condition， and the contact temperature of tooth surface increases with the increase of rotational speed， torque and backlash. The research results can provide a basis for the calculation and experimental measurement of the contact temperature of tooth surface.